2021
DOI: 10.3390/rs13214478
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Magnitude Estimation from High-Rate GNSS Data: A Case Study of the 2021 Mw 7.3 Maduo Earthquake

Abstract: Peak ground displacement (PGD) and peak ground velocity (PGV) are critical parameters during earthquake early warning, as they can provide rapid magnitude estimation before rupture end. In this study, we used the high-rate Global Navigation Satellite System (GNSS) data from 55 continuous stations to estimate the magnitude of the 2021 Maduo earthquake in western China. We used the relative positioning method and variometric approach to acquire real-time GNSS displacement and velocity waveforms, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…From the relocation results, we found that the aftershock sequence of the Maerkang earthquake moved southeastward and deeper underground (Figure 6). According to the analysis of regional tectonic stress research results, this is mainly due to the influence of the enormous stress environment of the block extrusion on the Tibetan Plateau, Like most other earthquakes in the Qinghai Tibet Plateau [49,50]. When the crustal material of the Tibetan Plateau migrated eastward, it was obstructed by the hard Sichuan Basin in the east to generate stress accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…From the relocation results, we found that the aftershock sequence of the Maerkang earthquake moved southeastward and deeper underground (Figure 6). According to the analysis of regional tectonic stress research results, this is mainly due to the influence of the enormous stress environment of the block extrusion on the Tibetan Plateau, Like most other earthquakes in the Qinghai Tibet Plateau [49,50]. When the crustal material of the Tibetan Plateau migrated eastward, it was obstructed by the hard Sichuan Basin in the east to generate stress accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the China Earthquake Information Network ( http://www.csi.ac.cn/ ), Maduo earthquake has the focal depth of 17 km, and the average altitude of 4,200 m within 10 km of the epicenter. Up to date, many scholars have kept on studying on the occurrence mechanism and induced geohazards of the 2021 Maduo earthquake (Chen et al, 2021 ; Gao et al, 2021 ; Wang et al, 2021 ; Zhu et al, 2021 ). However, we still know less about how will plant community responds to the earthquake in alpine grassland.…”
Section: Methodsmentioning
confidence: 99%
“…The left‐lateral strike‐slip Mw7.4 Maduo earthquake occurred on 21 May 2021, rupturing the near E‐W oriented JiangCuo fault, which is located within the Bayan Har block (Zhan et al., 2021) in the northeastern Tibetan Plateau (Figure 1b). The earthquake was well‐recorded in space geodetic images (He et al., 2022; J Liu et al., 2022) and nearby static (M. Wang, Wang, et al., 2022) and high‐rate Global Positional System (GPS) offsets (Gao et al., 2021). Earlier reports of the earthquake show that this was a bilateral rupture, which propagated ∼80 km to both sides of the epicenter (He et al., 2022; Ren et al., 2022; S. Wang, Song, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%